Quantitative analysis of effects of salvianic acid a combined with hydroxy safflower yellow a on rat endothelial cells after hypoxic injury using the combination index method - Zheyu Fang; Yuqi Ying; Weifeng Jin; Huaping Xu (Universidade de São Paulo, 2023)
Abstract Cerebrovascular disease is the second most serious disease in the world. It has the features of high morbidity, high mortality and recurrence rate. Numerous research on the compatibility of Chinese medicine with effective ingredients of cerebral ischemia has been made during the past decades. The purpose of this study is to quantitatively analyze the combined pharmacological effect of effective ingredients in Danshen and Honghua (Dan Hong) on rat microvascular endothelial cells after gradually oxygen-glucose deprivation. The experimental concentration range for the compatibility of two effective ingredients were determined in the preliminary experiments by Cell Counting kit-8 (CCK-8) method. Drugs were added to rat brain microvascular endothelial cells at a non-toxic dose level. After that, the cells were cultured for 12 h, and placed in a hypoxic environment. Finally, the cell survival rate was used as a measure of drug effect. In order to determine synergism or antagonism, the combination index (CI)-isobologram method was performed to analyze the data from the experiments. Based on this theory, the potencies of each drug and the shapes of their does-effect curves are both taken into account. The results show that the synergism or the antagonism between two effective ingredients compatibility change with different proportion and dosage. Furthermore, it can be seen from the results of these experiments that when these drugs are used in combination, the dosage required to achieve the same therapeutic effects is greatly reduced compared with the case of single one. It is worth mentioning that our experiments also prove that the median-effect equation and the CI method can be applied in the field of traditional Chinese medicine.